Reconditioning commercial vehicle booth from industrial bakery waste to support herbal products distribution in Menik Jaya Community Group - Dewa Kusuma Wijaya; Heru Agus Santoso; Herwin Suprijono; B.J. Ridwan Hartono; Rudi Tjahyono (Universitas Muhammadiyah Magelang, 2024)
The Menik Jaya Community Group faces constraints in distributing herbal products, impacting sales quality and quantity. Long distances, limited transportation, and weather-related product damage pose significant challenges. Additionally, bakery industry fiberglass booth waste presents an environmental issue. This community service aimed to address these problems by: 1) Providing more effective distribution through two-wheeled commercial booths; 2) Recycling fiberglass booth waste into functional commercial booths; and 3) Enhancing the group's herbal product marketing capacity. Methods included socialization, booth-making training, and commercial booth utilization assistance. Results yielded environmentally friendly commercial booths, improved distribution efficiency, and increased community income.